2012
DOI: 10.1002/asi.22677
|View full text |Cite
|
Sign up to set email alerts
|

A conversation analytic study of actual and potential problems in communication in library chat reference interactions

Abstract: Although chat-based reference services have been studied for over a decade and guidelines have been developed for effective communication in virtual reference service, little is known about the actual sources of miscommunication in these interactions. Our study uses a conversation analytic framework to investigate the types of potential or actual problems in communication that occur between librarians and patrons in chat reference interactions at a university library. Conversation analysis methodology, as deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Many of the CA investigations conducted so far in the fields LIS, communication research and education science have focussed on synchronous conversation occurring in chat forums (e.g. Gibson, 2009b; Koshik and Okazawa, 2012; Smithson et al , 2011). In terms of CA, studies such as these are limited in that they do not address the issues of expansion, due to the marginal role of quotes in chat discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the CA investigations conducted so far in the fields LIS, communication research and education science have focussed on synchronous conversation occurring in chat forums (e.g. Gibson, 2009b; Koshik and Okazawa, 2012; Smithson et al , 2011). In terms of CA, studies such as these are limited in that they do not address the issues of expansion, due to the marginal role of quotes in chat discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Later CA studies have enriched the picture of online talk by examining diverse issues such as intercultural communication online (Gibson, 2009a), the organisation of asynchronous discourse in a postgraduate reading group (Gibson, 2009b), the nature of problem presentation and responses on an asynchronous online forum for young people who self-harm (Smithson et al , 2011), and problems faced in library chat reference interactions (Koshik and Okazawa, 2012). More recently, Steensen (2014) combined the ideas of CA and content analysis in a study scrutinising conversations occurring in an interactive live blog.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A review of the literature on chat reference from 1995-2010 found 59 studies that focused on the parameters of the service (which clients were served and what questions they asked), the administration of the service (how questions were answered), staffing and training, and the purpose and objectives of the service (Matteson, Salamon, & Brewster, 2011). Since 2010, interest in the teaching potential for library chat has grown (Passonneau & Coffey, 2011;Dempsey, 2016;Dempsey, 2017), as has analysis of communication styles and problems (Radford, Connaway, & DeAngelis, 2011;Koshik & Okazawa, 2012;Owens, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apart from a few recent exceptions (Hui, 2018; Lockwood, 2017; Xu and Lockwood, 2021) scholarly examination of what exactly happens in web-based customer service interactions in business contexts is very scarce (see also Turel and Connelly, 2013). While digitally mediated customer service has been explored, previous studies focused on specific sites of talk, such as librarian-patron interactions (Fagan and Desai, 2003; Koshik and Okazawa, 2012), health counselling (Stommel, 2012; Stommel and Te Molder, 2015) or telephone sales (Clark et al, 2003; Mazeland, 2004). There is also a growing scholarship exploring customer service interactions with chatbots (Dippold et al, 2020).…”
Section: Introductionmentioning
confidence: 99%